1997
DOI: 10.1103/physrevlett.79.578
|View full text |Cite
|
Sign up to set email alerts
|

Production ofJ/ψMesons fromχcMeson Decays inet al.

Abstract: We have measured the fraction of J/psi mesons originating from chi(c) meson decays in p (p) over bar collisions at root s = 1.8 TeV. The fraction, for P-T/(J/psi) > 4.0 GeV/c and \(eta) over dot(J/psi) < 0.6, not including contributions from b flavored hadrons, is 29.7% +/- 1.7%(stat) +/- 5.7%(syst). We have determined the cross sections for J/psi mesons originating from chi(c) decays and for directly produced J/psi mesons. We have found that direct J/psi production is in excess of the prediction of the color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 243 publications
(119 citation statements)
references
References 21 publications
4
115
0
Order By: Relevance
“…It turns out that all three P-wave states, including 1 þþ are allowed. As we shall see, the color-singlet contributions give p T dependence, which is similar to the experimental data for c mesons, for example, from CDF [9], but the absolute normalization of the cross section is several times smaller than in the experiment. To resolve this contradiction we took into account the color-octet contributions to the cross sections.…”
Section: Introductionsupporting
confidence: 58%
“…It turns out that all three P-wave states, including 1 þþ are allowed. As we shall see, the color-singlet contributions give p T dependence, which is similar to the experimental data for c mesons, for example, from CDF [9], but the absolute normalization of the cross section is several times smaller than in the experiment. To resolve this contradiction we took into account the color-octet contributions to the cross sections.…”
Section: Introductionsupporting
confidence: 58%
“…The main reason is that the inclusive J=c production cross section already includes contribution from the C decays, which can amount to 20 Ä 30% [58,59]. If one excludes the expected contribution of C decays by taking the J=c production cross section to equal 0:8 Â 10: …”
Section: J=cmentioning
confidence: 98%
“…The direct production of J/ψ mesons is an important background at trigger level. Measurements at the Tevatron [133] have shown that predictions of the colour-singlet model, which is presently the one implemented in the pythia generator, underestimate the measurements by several orders of magnitude. Perturbative QCD is used in this model to generate cc pairs, which then hadronise to a charmonium state in a non-perturbative way.…”
Section: Event Generationmentioning
confidence: 99%